Efficacy of Commercial Disinfectants Against Black Root Rot (Berkeleyomyces rouxiae) and Verticillium Wilt (Verticillium dahliae) Pathogens of Cotton - Chi P. T. Nguyen; Brenda Vo; Duy P. Le (Agronomy)
Black root rot (BRR) and Verticillium wilt of cotton are caused by soilborne Berkeleyomyces rouxiae and Verticillium dahliae, respectively, and can individually cause yield loss of a 10–50% in New South Wales (NSW). Both diseases were first detected in a northern valley of NSW but are now present across the state. ‘Come Clean Go Clean’ is a widely practiced biosecurity measure used to minimize the risk of further introducing the pathogens from one field to another by restricting the movement of soil-contaminated farm equipment and machinery. We rely on cleaning agents to effectively wash down and decontaminate the equipment and machinery. In this study, we examined 12 locally available, commercial disinfectants for their efficacy against B. rouxiae and V. dahliae reproductive structures with and without soil contamination of 10% (w/v). We found a significant interaction between pathogens, disinfectants, and soil amendment (p < 0.01). The germination of B. rouxiae chlamydospores and endoconidia in both the presence and absence of soil contamination was completely suppressed even after a short 10 sec exposure to 70% ethanol and 25% bleach. Both 70% ethanol and bleach were highly lethal at 10 sec exposures in similar assays against V. dahliae microsclerotia and conidia. Some other commercial products were able to reduce the germination rate significantly but did not completely kill microsclerotia and conidia even after 30 min of exposure. The lethal effect against B. rouxiae and V. dahliae warrants further exploration of both 70% ethanol and bleach to improve their field applications. Additionally, the efficacy of most tested commercial disinfectants was time-dependent; however, this is not recommended on the labels for their effectiveness. This study provides an additional integrated disease management option aiming to limit the spread of the pathogens.